Hegel: Habit, Custom, and Government - Cesaroni, Pierpaolo (Conceptos Históricos, 2020)
The aim of this paper is to understand the relationship that exists, in Hegel’s philosophy, between his conception of “habit” and that of “the world of right”, insofar as both are defined by Hegel as “second nature”. First of all, we will focus on the Hegelian conception of habit, as it is formulated in his anthropology (first section of the philosophy of subjective spirit). Secondly, we will show the connection between the concept of habit and that of custom, as it is formulated in the philosophy of right. Finally, on this basis we will provide an insight into some of the fundamental structures of the Hegelian conception of the State as the “actuality of the ethical idea”.